Glutathione complexed Fe-S centers - Qi, Wenbin (2012)
Glutathione (γ-glutamyl-cysteinyl-glycine, GSH) is a major thiol-containing peptide with cellular levels of up to 10 mM.(1) Several recent reports have demonstrated glutaredoxins (Grx) to form [Fe2S2] cluster-bridged dimers, where glutathione provides two exogenous thiol ligands, and have implicated such species in cellular iron sulfur cluster biosynthesis. We report the finding that glutathione alone can coordinate and stabilize an [Fe2S2] cluster under physiological conditions, with optical, redox, Mossbauer, and NMR characteristics that are consistent with a [Fe2S2](GS)4 composition. The Fe–S assembly protein ISU catalyzes formation of [Fe2S2](GS)4 from iron and sulfide ions in the presence of glutathione, and the [Fe2S2] core undergoes reversible exchange between apo ISU and free glutathione.